NoTeb: NORDIC exploration of an early assessment framework in health care - Kari Jorunn Kvaerner; Linn N. Støme (Finnish Social and Health Informatics Association, 2019)
Nordic Test Beds (NoTeB) is a Nordic Innovation funded project to strengthen Nordic health care cooperation. By joining Nordic university hospitals and innovation centers, its aim has been to provide a Nordic test bed cooperation ecosystem that includes templates and tools for early decisional support. The objective of this study was to describe how the partners in the Nordic collaboration developed and agreed upon an early assessment framework in health care. The framework was also presented as a user guide with the aim of providing advisory guidelines accessible to health care institutions to support early assessment of health innovation. A co-creation process comprising all collaborating Nordic partners initiated by a workshop, sharing current practice and aligning needs and content of for a decision support tool. Large Nordic variation in value assessment approaches were found. For the decision-making tools, two important features were emphasized; the need for a decision support rather than a decision-making tool and that the tool should be based on valid measures; HTA- methodology. For the user guide, it was emphasized that it should be easily available in an easy-to-read report format. In conclusion, NoTeB was successful in uniting Nordic countries in a common objective to develop a decision-making tool and a user guide to assess health innovations. Although the tools and the guide are still to be tested, this is a first step in developing a standardized tool for innovation assessment among the Nordic countries.